Diretores iniciantes: desenvolvimento de um processo formativo em parceria - Silva, Kaori Giulianna Akatsu Caetano da (2021)
This study aims to devise a formative process in partnership with primary and secondary school principals who are newcomers in the public education system of a city in the countryside of São Paulo state. For the purposes of this research, a newcomer is a principal who has been in the role for no more than three years (HUBERMAN, 2000). We sought to identify the challenges they faced in their everyday activities; learn their strategies to tackle these challenges; identify and analyze their formative needs; and collaborate to devise strategies to deal with prioritized needs. Data collection was carried out through a questionnaire, presented to 21 school principals, and during four discussion groups attended by six school principals (WELLER, 2013). These meetings were later transcribed. Built upon the insights surfaced by the questionnaires, the group meetings aimed to validate and discuss newcome principals’ key challenges, strategies, and formative needs, as well as to devise a formative process to fulfill those needs. Data analysis was carried out based on prose analysis, as per discussions found in André (1983) and Lüdke & André (2013). We found that the challenges faced by newcome principals in the given education system are similar to those found in research projects of the kind. As in other contexts, key difficulties are related to lack of specific training for the role, scarce knowledge of bureaucratic and administrative procedures, little time available for pedagogical matters, people and conflict management, and lack of personnel. Our findings reinforce the relevance of previous and ongoing education for principals to perform their roles. The training proposal was completed based on the group’s input and the insights provided by the literature used in this study (LIBÂNEO, 2012, 2017, 2020; PARO, 1999, 2010, 2012, 2015), encompassing the importance of collective work and democratic, inclusive management. The study also suggests that newcome principals, as well as teachers, learn their job by doing it, which reinforces the importance of giving them space to discuss and reflect upon how they think and react, so that they can create strategies to face multiple challenges and transform their practice